Confessar a Morte: a Poesia Política de Anne Sexton e Sylvia Plath - Correia, Susana (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
This paper intends to show the importance of a political analysis of Anne Sexton’s and Sylvia Plath’s poetry, exploring the topic of death in the context of confessional poetry in the 1950s. I will consider the breakthrough that Robert Lowell’s Life Studies brought to the American literary scene, in a moment when a new Soviet, political and atomic threat hovered over America. In the eminence of nuclear fallout, the fight against communism explained the emergence of McCarthyism, a new isolationist strategy which aimed to detect the “enemy at home.” I will resort to concepts such as surveillance, containment and the death of privacy in the compared analysis of a selection of poems by Sexton and Plath, in order to demonstrate how both authors subverted the cult of domesticity and the mythical vision of the American family, which was a privileged way to preserve democratic values. Thus, I aim to evince that these women’s poetry is not only autobiographical, but also imminently political. Ultimately, I suggest that this poetry had a preponderant role in subverting the Cold War American social paradigm, offering an important and renewed insight of death, by exploring suicide and images of the wounded body as an atomic metaphor.